Evaluating the Impact of Youth Early Sport Specialization on Injury: An Evolution in Measurement - Todd Rockwood; Nicholas M. Edwards; Bradley Nelson; Julie Agel (SAGE Publishing, 2023)
Objective To track youth sports participation and injury occurrence accurately and longitudinally. Results An online survey tool that captures sports participation, frequency, level of competition, and tracks injury occurrence has been developed. The survey allows for longitudinal tracking of sports participation to evaluate the change from recreational to highly specialized sports participation. To maximize the utility of this research tool we identified swimmer plots which allow for clear visualization of the data as the best method for graphical representation. Implication Longitudinal measurement of sports participation to evaluate the impact of early sports specialization on injury is feasible with this tool and enhanced by the swimmer plots for visualization.